Biological Hydrogen Sulphide Removal from Air by Package Column - DURSUN, SUKRU (Asian Journal of Chemistry, 2010)
Many industrial processes and sewage treatment facilities produce odours, most of which are of decomposed sulphur compounds. Hydrogen sulphide, which is a toxic and corrosive gas, may be the standard indicator among the obnoxious odours and therefore the amount released into the air is required to be regulated strictly. Hydrogen sulphide was efficiently removed from contaminated air by a pilot-scale biofilter; a column prepared with soil, sawdust and activated sludge materials from the leather industry was used for preparation of a biodegradation unit. The biodegradation unit was used under several working conditions which were designed for 48 h repetition intervals, with different hydrogen sulphide concentrations, loading rate increased from 10 to 100 mg m-3 and different gas flow rates (25, 50 and 75 m s-1). The removal efficiencies of the biodegradation unit were measured mainly from the outflow concentrations and degradation activity. The main by-product obtained in the biodegradation process was sulphate in the drainage water, as it accounted for more than 90 % of the total sulphur compound decomposed in the packing material. Sulphate removal from the system was carried out by drainage water during the operation periods. In the recent study, about 100 % hydrogen sulphide removal was found at lower gas flow rates by the biologically produced reactor.